The Association between Provider Practice and Knowledge of ORS and Zinc Supplementation for the Treatment of Childhood Diarrhea in Bihar, Gujarat and Uttar Pradesh, India: A Multi-Site Cross-Sectional Study - Lamberti, Laura M.; Fischer Walker, Christa L.; Taneja, Sunita; Mazumder, Sarmila; Black, Robert E. (PloS one, 2015)
Programs aimed at reducing the burden of diarrhea among children under-five in low-resource settings typically allocate resources to training community-level health workers, but studies have suggested that provider knowledge does not necessarily translate into adequate practice. A diarrhea management program implemented in Bihar, Gujarat and Uttar Pradesh, India trained private sector rural medical practitioners (RMPs) and public sector Accredited Social Health Activists (ASHAs) and Anganwadi workers (AWWs) in adequate treatment of childhood diarrhea with oral rehydration salts (ORS) and zinc. We used cross-sectional program evaluation data to determine the association between observed diarrhea treatment practices and reported knowledge of ORS and zinc among each provider cadre. We conducted principal components analysis on providers' responses to diarrhea treatment questions in order to generate a novel scale assessing ORS/zinc knowledge. We subsequently regressed a binary indicator of whether ORS/zinc was prescribed during direct observation onto the resulting knowledge scores, controlling for other relevant knowledge predictors. There was a positive association between ORS/zinc knowledge score and prescribing ORS and zinc to young children with diarrhea among private sector RMPs (aOR: 2.32; 95% CI: 1.29-4.17) and public sector ASHAs and AWWs (aOR 2.48; 95% CI: 1.90-3.24). Controlling for knowledge score, receipt of training in the preceding 6 months was a good predictor of adequate prescribing in the public but not the private sector. In the public sector, direct access to ORS and zinc supplies was also highly associated with prescribing. To enhance the management of childhood diarrhea in India, programmatic activities should center on increasing knowledge of ORS and zinc among public and private sector providers through biannual trainings but should also focus on ensuring sustained access to an adequate supply chain.